Danger in Quicksand Swamp - Wallace, Bill, 1947- (New York : Holiday House, 1989)
Ben and Jake battle alligators, quicksand, and a murderer when they search for buried treasure on an island in a swamp.
Keywords: Buried treasure -- Fiction; Swamps -- Fiction